A Studied Some of the Thermal and Electrical Properties for Particulat Polymer Composites - Hadi, E. M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
This researchs the preparation of particulate polymer composites from Alkyd resin and Iraqi Burn Kaolin which were added as (20%,30%,40%,50%)and comparing with the polymer. It studied Thermal conductivity and Dielectric strength for both of the Alkyd resin and the Composite Material. The result showed an increase in Dielectric strength after adding the Iraqi Burn Kaolin , also the Thermal conductivity was increased by adding the Iraqi Burn Kaolin .